The Role of Linguistics in Fostering Cross-Cultural Awareness in an Era of Global Uncertainty: A Critical Discourse Analysis - Hutabarat, Yosanthi Shintike (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
In the era of global uncertainty—marked by rapid social, political, and economic changes—there is an increasing demand for cross-cultural awareness as a means to strengthen relationships among individuals from diverse cultural backgrounds. This study aims to examine the role of linguistics in fostering cultural awareness amid global uncertainty, focusing on the Critical Discourse Analysis (CDA) approach to understand the role of language as a tool to build awareness of cultural diversity and power dynamics in intercultural interactions. This research analyzes discourses present in various texts, including mass media, literary works, and everyday conversations, to identify how language practices can reinforce or challenge power relations between different cultural groups.The analysis reveals that language significantly influences global perceptions of cultural differences and can shape societal attitudes, perspectives, and values toward cultural diversity. This study emphasizes the importance of developing linguistic awareness as an integral part of cross-cultural education. Furthermore, literature, as a form of discourse practice, not only reflects cultural values but also serves as an ideological tool that can influence readers and expand their perspectives on the world's diversity and complexity. These findings highlight the necessity of multicultural education in fostering inclusive dialogue and sensitivity toward cultural differences in an increasingly interconnected world.